Biological Activities of Snowdrop (Galanthus spp., Family Amaryllidaceae) - Chee Kei Kong; Chee Kei Kong; Liang Ee Low; Liang Ee Low; Wei Sheng Siew; Wei-Hsum Yap; Kooi-Yeong Khaw; Long Chiau Ming; Andrei Mocan; Andrei Mocan; Bey-Hing Goh; Bey-Hing Goh; et al. (Frontiers Media S.A., 2021)
Snowdrop is an iconic early spring flowering plant of the genus Galanthus (Amaryllidaceae). Galanthus species (Galanthus spp.) are economically important plants as ornaments. Galanthus spp has gained significance scientific and commercial interest due to the discovery of Galanthamine as symptomatic treatment drug for Alzhiermer disease. This review aims to discuss the bioactivities of Galanthus spp including anticholinesterase, antimicrobial, antioxidant and anticancer potential of the extracts and chemical constituents of Galanthus spp. This review highlights that Galanthus spp. as the exciting sources for drug discovery and nutraceutical development.